Advances and technical standards in neurosurgery. Vol. 36 - Pickard, J. D. (John D.) (Advances and technical standards in neurosurgery, 2011)
This title features: Detecting residual cognitive function in disorders of consciousness (M.R. Coleman, J.D. Pickard); Rationale for hypothalamus-deep brain stimulation in food intake disorders and obesity (N. Torres, S. Chabardees, A.L. Benabid); Gustatory and reward brain circuits in the control of food intake (A.J. Oliveira-Maia, C.D. Roberts, S.A. Simon, M.A.L. Nicolelis); SEEG-guided RF-thermocoagulation of epileptic foci: A therapeutic alternative for drug-resistant non-operable partial epilepsies (M. Guaenot, J. Isnad, H. Catenoix, F. Mauguire, M. Sindou); Child abuse - some asp.